P143 Occupational causes of hypersensitivity pneumonitis from a UK regional database (2018 update). (December 2018) - Walters, GI; Mokhlis, JM; Robertson, AS; Moore, VC; Bhomra, PS; Burge, PS
Abstract : Introduction: The epidemiology of occupational hypersensitivity pneumonitis (HP) is changing, and metalworking fluid (MWF) exposure is now the commonest cause in the UK. 1 We have constructed a clinical database of patients with HP diagnosed at our UK-based regional referral service for occupational lung and interstitial lung diseases (ILD) from 2002 onwards; this has been recently updated and now contains demographic, exposure and diagnostic data for n=206 patients with HP of any cause. We aimed to review all cases with an occupational cause with respect to the causative exposure, diagnostic characteristics and compare with that of other established and unknown causes. Methods: We have collected patient data for 206 discrete cases of HP diagnosed at our ILD multidisciplinary team (MDT) meeting and/or occupational lung disease MDT meeting between 2002 and 2017. This included demographics (age, gender, ethnicity, smoking status), environmental and occupational exposures, clinical features, and diagnostic tests (CT imaging, bronchiolo-alveolar cell count, lung function, histology). We grouped the data by cause (occupational, non-occupational and unknown) and undertook hypothesis testing to look for differences between groups. Results: With respect to aetiology, HP cases were occupational (n=50), non-occupational (n=56) or unknown (n=100). The commonest causes of occupational HP were MWF (72%), moulds including humidifiers (10%), birds (8%) and household or commercial waste (6%). There were no chemical agents implicated, and only one case of farmers' lung. Occupational cases were significantly more likely than non-occupational cases to be young and male, with subacute or acute presentation, systemic and recurrent symptoms, fewer crackles, less reticulation on CT, and higher DLCO and KCO at presentation (all p=0.02 or less). Of the cases with an unknown cause 31% had no occupational history taken. Conclusion: MWF is the commonest cause of occupational HP at our UK regional referral service, where workers usually present with acute or subacute disease. Refuse and recycling work is an emerging cause of HP. A full occupational exposure history should be taken in cases where there is no apparent cause; these patients have predominantly chronic and fibrotic disease, where historical workplace exposures may be relevant. Reference: Barber CM, et al. Occup Environ Med2017;74:528–30.